2016
DOI: 10.1093/hmg/ddw267
|View full text |Cite|
|
Sign up to set email alerts
|

Vitamin B12 ameliorates the phenotype of a mouse model of DiGeorge syndrome

Abstract: Pathological conditions caused by reduced dosage of a gene, such as gene haploinsufficiency, can potentially be reverted by enhancing the expression of the functional allele. In practice, low specificity of therapeutic agents, or their toxicity reduces their clinical applicability. Here, we have used a high throughput screening (HTS) approach to identify molecules capable of increasing the expression of the gene Tbx1, which is involved in one of the most common gene haploinsufficiency syndromes, the 22q11.2 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Mice under-expressing Tbx1 recapitulate the 22q11.2 deletion phenotype [ 8 ]. It is noteworthy that vitamin B12 is one of two compounds identified in high throughput screening that upregulates Tbx1 expression and rescues the 22q11.2 deletion phenotype in mice [ 9 ], which is consistent with our findings in the patient.…”
Section: Discussionsupporting
confidence: 90%
“…Mice under-expressing Tbx1 recapitulate the 22q11.2 deletion phenotype [ 8 ]. It is noteworthy that vitamin B12 is one of two compounds identified in high throughput screening that upregulates Tbx1 expression and rescues the 22q11.2 deletion phenotype in mice [ 9 ], which is consistent with our findings in the patient.…”
Section: Discussionsupporting
confidence: 90%
“…In particular, it demonstrated that vitamin B12 treatment partially rescued pharyngeal arch artery defects. These findings aroused hope for potential pharmacological strategies that could compensate for developmental defects in patients with 22q11.2DS (Lania et al, 2016). …”
Section: Genes and Pathogenesis Of The Cardiovascular Phenotypementioning
confidence: 99%
“…In the second case, because, although it has been shown that there is a low prevalence of growth hormone deficiency in 22q11.2DS individuals, those patients with this endocrine disorder treated with growth hormone show growth improvement [36], even when an adequate dietary intake showed no results [71]. In the last case, given that CHD is commonly observed in patients and a recent study shows promising results that suggest that the embryonic treatment using vitamin B12 ameliorates Tbx1 gene haploinsufficiency in mice [72]. This latter result could be relevant for the population analyzed in the present study, since CHD was highly prevalent (91.9%) in patients, as it has been reported in a previous study of Mexican patients [73].…”
Section: Discussionmentioning
confidence: 99%